2020
DOI: 10.1111/jocd.13362
|View full text |Cite
|
Sign up to set email alerts
|

Effective combination therapy with high concentration of Minoxidil and Carboxygas in resistant Androgenetic alopecia: Report of nine cases

Abstract: Background Androgenetic alopecia (AGA) is widely characterized as the main reason of hair loss which most of the time it has been reported in adults regarding dermatological consultation. Also, it is broadly believed that the progressive miniaturization of hair follicles could be usually different at the age of onset. Aims Over the last decade, detecting and understanding newer genetic basis in AGA lead to provide better therapeutic approaches. We have highlighted on an evidence‐based method to treat AGA whose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 11 publications
(34 reference statements)
0
14
0
Order By: Relevance
“…The pharmacological effects of minoxidil include 1 (A) increasing blood circulation, because it can induce vasodilation and contribute to the overexpression of vascular endothelial growth factor; (B) accelerating the mitosis of hair matrix keratinocytes, promoting hair growth, and increasing hair diameter; (C) extending the growth period of hair follicles; (D) stimulating hair follicles to start a new growth cycle. Recent studies have revealed that 5% minoxidil is more effective than 2% minoxidil, which is used twice a day for 1 year (40% increase in reaction rate) 19 . In 2016, 5% minoxidil foam was approved for male androgenic alopecia (MAGA).…”
Section: Discussionmentioning
confidence: 99%
“…The pharmacological effects of minoxidil include 1 (A) increasing blood circulation, because it can induce vasodilation and contribute to the overexpression of vascular endothelial growth factor; (B) accelerating the mitosis of hair matrix keratinocytes, promoting hair growth, and increasing hair diameter; (C) extending the growth period of hair follicles; (D) stimulating hair follicles to start a new growth cycle. Recent studies have revealed that 5% minoxidil is more effective than 2% minoxidil, which is used twice a day for 1 year (40% increase in reaction rate) 19 . In 2016, 5% minoxidil foam was approved for male androgenic alopecia (MAGA).…”
Section: Discussionmentioning
confidence: 99%
“…Microneedling for AGA has been used either alone, 20 with saline solution, as a drug delivery system with minoxidil, [19][20][21][22][23][24] or with growth factors and PRP. [25][26][27][28] Other subsequent studies focused on the Platelet-rich plasma (PRP) combined with microneedling.…”
Section: Microneedling For Androgenetic Alopeciamentioning
confidence: 99%
“…Microneedling for AGA has been used either alone, 20 with saline solution, as a drug delivery system with minoxidil, 19‐24 or with growth factors and PRP 25‐28 …”
Section: Microneedling For Androgenetic Alopeciamentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, many techniques were used for the alopecia 3,4 . The most common methods for the androgenetic alopecia treatment are the topical minoxidil, the finasteride pills, and hair transplantation 5‐7 . Studies reported that traditional treatments are only a little effective in the androgenetic alopecia treatment 4 .…”
Section: Introductionmentioning
confidence: 99%